(untitled) (Journal of the College of Basic Education, 2022)
The men of Iraq were characterized by their intellectual competencies and their mastermind mental abilities to solve the most difficult dilemmas and solve mysteriesThe most complex adversities and hardships, so it established firm feet to achieve the demands and achieve the best goals. Her valiant courageTo fight the battles and storm the lightning with unyielding determination and strength that does not weaken. They remember the battles they fought, especiallyagainst the British occupation of Iraq (1932-1914); This does not mean that the Iraqis did not resist the occupationottoman before; Rather, this occupation entered Iraq in the capacity of that Muslim liberator, and the battle of Shuaiba is not general4 is the best evidence for our saying.